Deep Ultraviolet CMOS-Controlled Micro Light-Emitting Diode Array - Jonathan J. D. McKendry; Enyuan Xie; Jordan Hill; Hichem Zimi; Johannes Herrnsdorf; Erdan Gu; Robert K. Henderson; Martin D. Dawson (IEEE Photonics Journal)
We report a Deep Ultraviolet (DUV) AlGaN micro-light emitting diode (micro-LED) array driven by a matching array of electronic drivers implemented in Complementary Metal-Oxide-Semiconductor (CMOS) technology. This 40 × 10 pixel integrated device required improvements in micro-LED fabrication combined with control over the LED ground level in the custom designed CMOS chip. It allows each of the micro-LEDs, with a measured peak emission wavelength of 271 nm, to be addressed independently in continuous wave (CW) or nanosecond pulsed operation, with optical output powers and pulse energies per pixel of 80 μW and 0.2 pJ, respectively. Performance of this high-resolution electronically-driven array for multi-channel UV-C wireless communications is given as an example of its potentially wide-ranging uses.